HUBUNGAN DUKUNGAN SOSIAL DENGAN BURNOUT BELAJAR PADA SISWA KELAS XI DI SMA NEGERI 4 YOGYAKARTA - Fani Rahmasari (Journal of Innovative Counseling : Theory, Practice, and Research, 2017)
This research is aimed to find out the relationship between social support and burnout of students’ learning of Grade XI students SMA N 4 Yogyakarta year 2015-2016. The research used quantitative approach and the type of research was correlation. Subject of the research were 258 students of grade XI SMA Negeri 4 Yogyakarta. In addition, the sampling technique was cluster random sampling. The samples consisted of 5 classes of 146 students. The data collection used was social support and burn out scale. The validity was referred to expert judgment in social support scale meanwhile burnout learning had validity rate of P>0,01. The reliability test result using Cronbach Alpha was 0,862 for burnout learning and 0,946 in social support scale. Data analysis of the research used Pearson’s product moment using SPSS for Windows version 22.0. The result of the research showed the negative relationship and significant between social support burnout learning of grade XI students SMA Negeri 4 Yogyakarta, the relationship correlation value was -0,417 as the significance was p=0.000<0,05, means that the higher the social support is the lower burnout learning and vice versa. The determinant value (R square) was 0,714 could be defined as social support gave contribution of 17,4 % against burnout. The rest of 82,6% variable was caused by other variables in this research.